PASTURE MANAGEMENT STRATEGIES BASED ON FORAGE OFFER ALTER THE STRUCTURE OF XARAES PALISADEGRASS - Janusckiewicz, E. R. [UNESP]; Raposo, E. [UNESP]; Casagrande, D. R.; Ruggieri, A. C. [UNESP] (Inst Zootecnia, 2017)
Forage offers can be used as a pasture management strategy that considers both the plant and the animal. Therefore, the objective of this study was to evaluate the pre- and post-grazing structure of Brachiaria brizantha cv. Xaraes pastures managed by offering forage at 4, 7, 10 and 13 kg dry matter (DM)/100 kg body weight (BW). The pastures were managed under mob stocking of Holstein cows, with one day of grazing and 21 days of rest. Pre-grazing height increased with forage offer. An increase in post-grazing heights was observed at 13 kg DM/100 kg BW. Pre-grazing leaf and stem percentage or leaf: stem ratio was not influenced by forage offer, but there was a quadratic effect on post-grazing leaf percentage and a linear effect on post-grazing stem percentage. Considering that an increase in forage offer increased post-grazing forage mass and stem percentage, the use of forage at 7 and 10 kg DM/100 kg BW is indicated.
Keywords: bulk density; plant height; specific leaf area; stem; grazing intensity